IMPACT OF ULTRAFINE AIR POLLUTANTS ON AMYLOID PEPTIDE STRUCTURE AND OLIGOMERIZATION - Kaumbekova, Samal (School of Engineering and Digital Sciences, 2023)
Amyloid beta (Aβ) peptide monomers aggregate into toxic oligomers in the human brain, leading to the progression of Alzheimer's Disease (AD), one of the common types of neurodegenerative diseases. Lifelong exposure to ambient air pollution and, particularly, ultrafine particles (UFPs) is associated with an elevated risk of the progression of AD. While the experimental studies revealed the negative impact of air pollutants on AD, the molecular interactions remain unknown. The objective of this research was to investigate the impact of ambient air pollutants on the structure and oligomerization of Aβ peptide monomers via atomistic molecular dynamics (MD) simulations, which were not demonstrated earlier. Considering the complex composition of the ambient UFPs, which usually include water-soluble ions, organic carbon (OC), elemental carbon (EC), and trace elements, this work elucidated the effect of the various compositions and concentrations of the ambient air pollutants on Aβ peptides. The systems under the study were divided as follows: i) the effect of concentration of hydrophobic UFP, modeled by C60 (EC), ii) the effect of the water-soluble ions (NO3−, NH4+,SO42−), iii) the effect of the cigarette smoke components, represented by nicotine and polycyclic aromatic hydrocarbons (PAHs), such as benzo[a]pyrene (B[a]P) and phenanthrene, iv) effect of the carbonaceous UFPs. Overall, the results of this study revealed that both the composition and concentration of air pollutants affect the structure of Aβ peptide monomers and consequent oligomerization. In particular, while the EC accelerated the oligomerization in the presence of SO42− and NO3− ions, the oligomerization was inhibited in the presence of C60 and NH4+ ions, showing the synergistic effect of EC and ambient water-soluble ions. Considering the molecular mechanisms, it should be noted that oligomerization and the growth of peptide oligomers on the surface of carbonaceous UFP models were driven by strong hydrophobic interactions. Moreover, the experimental validations demonstrated alterations in the secondary structure of Aβ peptides and enhanced growth of the β-sheets in the presence of NH4+, as well as a suppressed growth of the β-sheets in the NO3− environment due to the enhanced interactions between the peptides and nitrates. Furthermore, according to the results of the MD study, PAHs and nicotine altered the secondary structure of the Aβ monomer. Moreover, although nicotine made H-bonds with the Aβ42 monomer, resulting in the formation of a stable intermolecular cluster, phenanthrene, due to its small size, had a most significant interference with the Aβ42 monomer. In addition, B[a]P with 5 mM concentration accelerated the oligomerization of four Aβ42 peptide monomers, while the presence of B[a]P with higher concentrations suppressed the oligomerization kinetics. Lastly, the carbonaceous UFPs accelerated the early aggregation of the peptide monomers to dimers, suggesting their contribution to the progression of AD. The insights revealed from this study would be helpful for the improvement of the existing policies on the reduction of air pollution, as well as for the development of new therapeutics aimed to mitigate the effects of air pollution on the progression of AD.
Keywords: type of access: open access; ultrafine air pollutants; amyloid peptide structure; oligomerization